L’adaptation de la gestion des espaces naturels urbains aux changements de la variabilité climatique régionale : exemple de Paris et Montréal - Guillaume Simonet; Nathalie Blanc (VertigO, 2012)
This contribution aims to outline the respective roles of adaptation to climate change and biodiversity in the elaboration of urban sustainability policies through two case studies located in Paris and Montreal. This work was driven through semi-structured interviews with officials of the City of Paris and of Montreal. This study, more narrowly, aims to detect the existence of links between the management of parks and gardens and adaptation to climate change. Through content analysis of interviews, the article tries to explain the differences between the policies pursued by the cities of Paris and Montreal, knowing that, as part of this article, we will content ourselves with sketching the beginnings. To achieve this, we will focus on the stories of actors, their findings on climate change as part of their ordinary activities on the reflections generated and the responses given. The comments gathered show that the adaptive management of natural areas urban changes in climate variability is based on the priority given to native plant species considered most appropriate to regional biophysical conditions.